2013
DOI: 10.3109/09638288.2013.814722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fear of falling on gait and balance in Parkinson’s disease

Abstract: Purpose To study the relationship of fear of falling (FoF) with gait characteristics and balance in individuals with Parkinson’s disease (PD). Method Seventy-nine non-demented individuals (62 males) with PD were studied. Their mean age was 69.22 ± 8.93 years. The average time since diagnosis was 8.27 ± 5.31 years. FoF was assessed by the Activities-specific Balance Confidence (ABC) Scale in which high scores indicate less FoF. Gait was measured using a computerized walkway. Balance was measured by timed test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
42
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 33 publications
(50 reference statements)
9
42
2
1
Order By: Relevance
“…The amount of COP ML ApEn in moderate and sever PD while standing on foam surface with open eyes is so high that could not increase more by eye closure as it might cause clinical instability and falling so these patients show this conservative behavior (not significant increase of COP irregularity) in such a high demand condition but its value in mild PD is not the maximum in same condition so it would increase by going to more difficult situation. Fear of falling could be a reason for such a behavior in individuals with more sever PD(41,42) which high correlation of FES (Falls Efficacy Scale)(43) and H/Y scale scores in this study confirms (p≤0.000, Spearman's Correlation= -0.652). An investigation, using SOT and linear COP measures has demonstrated postural instability in those with PD in first three stages of disease, based on H/Y scale, when in challenging or conflicting sensory conditions necessitating the use of vestibular system(44).…”
supporting
confidence: 79%
“…The amount of COP ML ApEn in moderate and sever PD while standing on foam surface with open eyes is so high that could not increase more by eye closure as it might cause clinical instability and falling so these patients show this conservative behavior (not significant increase of COP irregularity) in such a high demand condition but its value in mild PD is not the maximum in same condition so it would increase by going to more difficult situation. Fear of falling could be a reason for such a behavior in individuals with more sever PD(41,42) which high correlation of FES (Falls Efficacy Scale)(43) and H/Y scale scores in this study confirms (p≤0.000, Spearman's Correlation= -0.652). An investigation, using SOT and linear COP measures has demonstrated postural instability in those with PD in first three stages of disease, based on H/Y scale, when in challenging or conflicting sensory conditions necessitating the use of vestibular system(44).…”
supporting
confidence: 79%
“…The mean ABC score of the participants was relatively high, and many of the items of the instrument inquire about balance confidence during basic gait and mobility tasks similar to the outcome tasks we were measuring. Gait velocity in preferred-pace forward and backward gait was previously shown to be lower in individuals with PD with fear of falling as measured by the ABC (regardless of fall history), and similarly time to complete the TUG was higher in these individuals, supporting the relevance of the ABC for these basic gait and mobility outcomes (Bryant et al, 2014). Despite not containing turning-specific items, balance confidence was most relevant in predicting TUG, which could potentially be attributed to the presence of turning during this task.…”
Section: Discussionmentioning
confidence: 69%
“…Disparities in testing protocols and disease duration between the samples (mean 13 years), compared to the current study (mean 6 years) may account for these observed differences (Sustakoski, Perera, VanSwearingen, Studenski, & Brach, 2015). Although similar investigations of the relationships between the Walk‐12G and performance‐based gait measures are lacking, fear of falling has been associated with slower gait speeds in healthy older adults (Maki, 1997) and people with PD (Bryant, Rintala, Hou, & Protas, 2014; Rochester et al., 2008). Additionally, Curtze et al.…”
Section: Discussionmentioning
confidence: 99%